Benefits to speech perception in noise from the binaural integration of electric and acoustic signals in simulated unilateral deafness - Ma, Ning; Morris, Saffron D.; Kitterick, Pádraig T. (Lippincott, Williams & Wilkins, 2016)
Objectives: This study used vocoder simulations with normal-hearing (NH) listeners to (a) measure their ability to integrate speech information from a NH ear and a simulated cochlear implant (CI); and (b) investigate whether binaural integration is disrupted by a mismatch in the delivery of spectral information between the ears arising from a misalignment in the mapping of frequency to place.